2011
DOI: 10.1128/jcm.02548-10
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Differentiation of Methicillin-Resistant and Methicillin-Susceptible Staphylococcus aureus by Flow Cytometry after Brief Antibiotic Exposure

Abstract: We noticed that methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) isolates yielded side-scatter (SSC) and fluorescence intensity (FI) differences on flow cytometry (FCM) following incubation in oxacillin broth. The purpose of this study was to determine whether MRSA and MSSA could be reliably differentiated by FCM. S. aureus isolates were incubated in oxacillin-containing MuellerHinton broth, stained using the FASTEST total viable organisms kit, and analyzed by FCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…Our previous study showed that given a suspension of S. aureus, one can differentiate MRSA from MSSA by flow cytometry using a dye that stains nucleic acid in a nonspecific manner (5). The present study shows that the same differentiation can be achieved using an S. aureus-specific dye instead of the nonspecific nucleic acid dye.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Our previous study showed that given a suspension of S. aureus, one can differentiate MRSA from MSSA by flow cytometry using a dye that stains nucleic acid in a nonspecific manner (5). The present study shows that the same differentiation can be achieved using an S. aureus-specific dye instead of the nonspecific nucleic acid dye.…”
supporting
confidence: 65%
“…We have previously demonstrated that methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-susceptible S. aureus (MSSA) isolates can be accurately and rapidly differentiated by flow cytometry based on fluorescence intensity and side scatter differences after brief exposure to oxacillin, using a nonspecific fluorescent nucleic acid dye (5). Flow cytometry to differentiate MRSA from MSSA would be even more useful if the method could incorporate S. aureus-specific probe labeling instead of using a nonspecific dye.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During susceptibility testing, the ratio between dead and/or non-dividing cells changes over time and the use of fluorescent labeling and FACS can then help to determine the bactericidal or bacteriostatic effect of the antibiotic studied. It has been shown that methicillin susceptible S. aureus (MSSA) and methicillin resistant S. aureus (MRSA) can be distinguished by FACS after two-hour incubation with oxacillin [95]. When using micro-fluidic methods in combination with FACS, one can also distinguish cellular shapes and sizes.…”
Section: Immediate Urgenciesmentioning
confidence: 99%
“…COSTA-DE-OLIVEIRA; RODRIGUES, 2005;SHRESTHA et al, 2011;VALE-SILVA et al;WANG et al, 2014). BANCALARI et al, 2016;NOBLE, 1999).…”
unclassified